2002
DOI: 10.1677/joe.0.1750727
|View full text |Cite
|
Sign up to set email alerts
|

Isoproterenol is a positive regulator of the suppressor of cytokine signaling-3 gene expression in 3T3-L1 adipocytes

Abstract: SOCS (suppressor of cytokine signaling)-3 has recently been shown to be an insulin-and tumor necrosis factor (TNF)--induced negative regulator of insulin signaling. To further clarify a potential involvement of SOCS-3 in the development of insulin resistance, we measured differentiation-dependent SOCS-3 mRNA expression in 3T3-L1 adipocytes and studied its regulation by various hormones known to impair insulin signaling using quantitative real-time RT-PCR. There was a differentiationdependent downregulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 39 publications
0
16
1
Order By: Relevance
“…They include upregulation of IRS-1, the p85 subunit of phosphatidylinositol 3-kinase (PI3-kinase), thymoma viral proto-oncoprotein (Akt), growth factor receptor-bound protein 2 (Grb2), growth factor receptorbound protein 10 (Grb10), and extracellular signal-regulated kinase 1 (Erk1) and downregulation of SOCS3, an inhibitor of insulin signaling. It has been shown that activation of the PI3K/ Akt pathway is required for insulin-induced adipogenesis (1,34,58,60), while adipocyte differentiation is associated with downregulation of SOCS3 expression (12). Thus, the coordinated regulation of insulin signaling components by BMP7 suggests that BMP7-induced adipogenesis is mediated at least partly by enhancing insulin signaling.…”
Section: Bmp7 Induces Expression Of Insulin Signaling Components In Mmentioning
confidence: 99%
“…They include upregulation of IRS-1, the p85 subunit of phosphatidylinositol 3-kinase (PI3-kinase), thymoma viral proto-oncoprotein (Akt), growth factor receptor-bound protein 2 (Grb2), growth factor receptorbound protein 10 (Grb10), and extracellular signal-regulated kinase 1 (Erk1) and downregulation of SOCS3, an inhibitor of insulin signaling. It has been shown that activation of the PI3K/ Akt pathway is required for insulin-induced adipogenesis (1,34,58,60), while adipocyte differentiation is associated with downregulation of SOCS3 expression (12). Thus, the coordinated regulation of insulin signaling components by BMP7 suggests that BMP7-induced adipogenesis is mediated at least partly by enhancing insulin signaling.…”
Section: Bmp7 Induces Expression Of Insulin Signaling Components In Mmentioning
confidence: 99%
“…Our current findings suggest that downregulation of visfatin in adipocytes may contribute to impaired glucose tolerance caused by increased GH levels. However, it has to be pointed out that stimulation of suppressor of cytokine signaling (SOCS)-1 (Fasshauer et al 2004b) and -3 (Fasshauer et al 2002), activation of MCP-1 (Fasshauer et al 2004a) and IL-6 (Fasshauer & Paschke 2003), as well as altered insulin signaling downstream of phosphatidylinositol 3-kinase (Takano et al 2001), are additional mechanisms by which GH affects glucose metabolism.…”
Section: Figurementioning
confidence: 99%
“…In 3T3-L1 adipocytes significant impairment of insulin-stimulated glucose uptake is seen after treatment with 4 µM isoproterenol for 16 h (Kaestner et al 1991). Several mechanisms by which catecholamines induce insulin resistance have been suggested, including molecular interactions on several levels between adrenergic and insulin signaling cascades (Klein et al 1999, Klein et al 2000, upregulation of IL-6 (Fasshauer & Paschke 2003) and SOCS-3 (Fasshauer et al 2002), as well as suppression of adiponectin (Fasshauer & Paschke 2003). Based on the findings in our current study, downregulation of the insulinmimetic visfatin may also contribute to catecholamineinduced glucose intolerance.…”
Section: Figurementioning
confidence: 99%
“…Recently, we and others have demonstrated that GH, TNF , insulin and -adrenergic agonists stimulate SOCS-3 mRNA expression and that SOCS-3 inhibits insulin signaling in 3T3-L1 adipocytes (Emanuelli et al 2000, 2001, Fasshauer et al 2002. Furthermore, it has been shown that SOCS-1 and -6 are also potent inhibitors of insulin signaling (Mooney et al 2001, Rui et al 2002, and it appears plausible that cytokines such as TNF , GH, and IL-6 might further decrease insulin sensitivity in fat cells by upregulating either of these proteins.…”
Section: Introductionmentioning
confidence: 99%